A Case of Pulmonary Epithelioid Hemangioendothelioma with Literature Review. (8th October 2020) - Aung, Thu Thu; Chu, Andrew; Kondapi, Divya; Markabawi, Danny; Mirchia, Kanish; Kaul, Pratibha
Abstract : Pulmonary epithelioid hemangioendothelioma is a rare vascular tumor and infrequently described in medical literature as case reports and case series. Diagnosis is often incidental with high index of histopathological suspicion from clinical pathologist. The pathological pattern is quite unique with distinct immunohistochemical stains. Up to this day, there is no established standard treatment owing to the scarcity of this tumor. In this case report, we describe a case of pulmonary epithelioid hemangioendothelioma unexpectedly diagnosed with transthoracic needle biopsy, along with a review of the current literature.